Developing a Digital Pop-Culture Zone Media Based on STAD Models to Improve Students’ Reading Comprehension - Nadia, Isna Ahsanu; Purwati, Panca Dewi (Journal of Language and Literature Studies, 2026)
Reading skills are very important for elementary school students to master in order to improve their learning outcomes. Lack of reading comprehension skills is a problem for fifth graders. Therefore, this study was conducted to help students improve their reading comprehension skills. The purpose of this study was to develop, test the feasibility, and test the effectiveness of digital pop culture zone media based on the student team achievement division (STAD) model to improve the reading comprehension of fifth graders. This study used the Research and Development (R&D) method by Borg and Gall in Sugiyono's book, which is abbreviated into eight stages, including potential and problems; data collection; product design; design validation; design revision; preliminary testing; product revision; and usage testing. This study developed digital pop-culture zone media based on the STAD model. Digital pop-culture zone media is highly suitable for application with the six steps of the STAD model because it helps students become more active in group discussions as a way to improve their reading comprehension. The results of the expert assessment of the media and materials reached 91.67% and 95% with a very feasible criterion, and obtained scores of 92.85% and 96% for the results of the teacher and student response questionnaires with a very feasible criterion for the media and model used. Therefore, STAD-based digital pop culture zone media is declared to be very feasible and effective for improving reading comprehension.